Western blot analysis of glucocorticoid receptor phosphoisoforms by one- and two-dimensional electrophoretic assays - CONSTANTINOS DEMONACOS; MARIJA B. RADOJČIĆ; MIROSLAV ADŽIĆ; ANA NIĆIFOROVIĆ; NATAŠA POPOVIĆ; MARIJA KRSTIĆ-DEMONACOS (Journal of the Serbian Chemical Society, 2009)
The glucocorticoid receptor (GR) protein is a cytosolic ligand-dependent transcription factor with numerous functions regulated by post-translational modifications, including phosphorylation/dephosphorylation. Among the functions most extensively affected by GR phosphorylation are the modulation of its transcriptional activity, alterations in its interaction pattern with cofactors, nuclear translocation and selective gene transactivation. Intensive analysis of the intracellular distribution of GR phosphoisoforms and their interaction with proteins of other cellular signalling networks required the use of [-32P]ATP as a phosphate donor, and special laboratory protection measures to avoid external irradiation and contamination. In the present study, simple and easy-to-use non-radioactive protein mobility shift assays (NMS assays) were developed using one- and/or two-dimensional gel electrophoresis based on differences in the pI and molecular mass of GR phosphoisoforms. The GR isoforms were immunodetected with specific monoclonal or polyclonal anti-GR antibodies by Western blot in three diverse systems, namely yeast BJ2168 cells expressing wild-type rat GR, rat hepatoma GRH2 cells grown in culture and brain tissue from Wistar rat experimental animals. The results obtained using the NMS assay were similar to previous results obtained with the [-32P] ATP standard assay.